Microsoft Sharepoint Portal Server : - Laahs, Kevin (Digital Press, 2002)
Use Microsoft SharePoint Portal Server 2001 as a foundation for building knowledge sharing applications. This book details how IT professionals can plan, design and implement web based solutions using Microsoft's Intranet Portal. Written by experts from Compaq, the world's prime integrator of Exchange systems and Microsoft's Partner of the Year, the book illustrates how easy it is to create sophisticated knowledge based applications using SharePoint Portal Server. It provides an excellent overview of the built-in features and functionality of SharePoint Portal Server, and describes how a Portal coordinator can easily customize the product to fit their business needs.